VISITOR SATISFACTION ANALYSIS OF CREATIVE INDUSTRY IN TOURISM LOCATIONS USING SERVQUAL METHOD - Aggy Pramana Gusman; Harkamsyah Andrianof; Silky Selfira (Jurnal Ipteks Terapan, 2020)
The development of Padang City as a city that carries the creative industry began to be felt after the transition fromthe earthquake in 2009. The city of Padang began to improve to become the center of the creative industry in WestSumatra. The large variety of carvings and famous food and handicrafts has made the potential realm of MiningMajadi the national and foreign spotlight. Creative work produced by the community has become a trend inIndonesia, especially among the younger generation. The creative industry that is developing in Padang City hasmade a significant contribution, but has not been managed properly and has an impact on overlapping functions ofthe area and causes inconvenience for tourists. The research method used in this study is the Servqual Method. Thedata collection method used is divided into two activities, namely primary surveys consisting of field observations,interviews, and distributing questionnaires and secondary surveys consisting of literature studies and data collectionthrough related agencies. The research object is the creative industry in the city of Padang. This research producescalculations with the method Servqual, there are four attributes that have the highest gaps, namely the level ofservice fulfillment that is still far from the level of customer expectations. These attributes includecomfort/facilities/, tour guides can explain information clearly, friendliness. Location near creative industries closeto tourism locations, discounts on services, and materials.